2017
DOI: 10.5010/jpb.2017.44.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Sugar content analysis and expression profiling of sugar related genes in contrasting Strawberry (Fragaria × ananassa) cultivars

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract Fragaria × ananassa, a strawberry evolved from hybridization between F. virginiana and F. chiloensis, is a globally cultivated and consumed fruit crop valued for its flavor and nutritional value. Flavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…Sucrose content was the highest among that of all the soluble sugars present in the fruits of the high sugar-content cultivars, ranging between 4.399 ± 0.017 and 7.571 ± 0.021 g/100g, while glucose content was the lowest, ranging from 1.331 ± 0.001 to 3.079 ± 0.006 g/100g (Table 1). Sugar content and the ratio of soluble sugar concentration in the high sugar-content cultivars showed a similar trend to that previously reported for the cultivars Maehyang, Seolhyang, Festival, and Sweet Charlie (Shanmugam et al 2017). In the case of the low sugarcontent cultivars, fructose content was the highest (2.461 ± 0.007 g/100g -2.799 ± 0.011 g/100g), while sucrose content was the lowest (0.352 ± 0.003 g/100g -0.628 ± 0.011 g/100g) among all the soluble sugars quantitated (Table 1).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Sucrose content was the highest among that of all the soluble sugars present in the fruits of the high sugar-content cultivars, ranging between 4.399 ± 0.017 and 7.571 ± 0.021 g/100g, while glucose content was the lowest, ranging from 1.331 ± 0.001 to 3.079 ± 0.006 g/100g (Table 1). Sugar content and the ratio of soluble sugar concentration in the high sugar-content cultivars showed a similar trend to that previously reported for the cultivars Maehyang, Seolhyang, Festival, and Sweet Charlie (Shanmugam et al 2017). In the case of the low sugarcontent cultivars, fructose content was the highest (2.461 ± 0.007 g/100g -2.799 ± 0.011 g/100g), while sucrose content was the lowest (0.352 ± 0.003 g/100g -0.628 ± 0.011 g/100g) among all the soluble sugars quantitated (Table 1).…”
Section: Resultssupporting
confidence: 88%
“…It has been reported that fructose and glucose are the main sugars in strawberries from the analysis of Festival, Sweet Charlie, Camaraso, Selva, and 12 other cultivars mainly grown in the USA and Europe. (Castro et al 2002;Sturm et al 2003;Shanmugam et al 2017). In this study, two contrasting groups of cultivars differed in their respective sugar composition; sucrose was the main sugar present in the high sugar-content cultivars, while fructose prevailed in the low sugar-content cultivars.…”
Section: Resultsmentioning
confidence: 66%
“…Both metabolic patterns and concentration are highly variable according to the species. In this vein, accumulation of sucrose, glucose, and fructose during ripening are especially observed in sweet fruits such as apples ( Jakopic et al, 2018 ; Williams and Benkeblia, 2018 ), litchi ( Yang Z. et al, 2013 ), melons ( Burger et al, 2000 ; Huang et al, 2017 ), peach ( Cirilli et al, 2016 ), strawberries ( Shanmugam et al, 2017 ), mango ( Cosme Silva et al, 2017 ), papaya ( Paull et al, 1999 ) and watermelons ( Liu et al, 2013 ) (Table 2 ). In general, sugar accumulation in fruit is directly controlled by increasing the activities of sucrose synthase (Suzy) and SPS ( Chen et al, 2004 ).…”
Section: The Metabolic Behavior Of Organic Acids During Fruit Developmentioning
confidence: 99%
“…Four SNP markers (MF518, MF1321, MF1169, and MF3696) located at the peak LOD positions of the corresponding SSC related QTLs and one SNP (marker MF154) on the gene FAN_iscf00021287, a key candidate gene for sugar biosynthesis (Shanmugam et al 2017 ) located within the flanking region of QTL qSSC-5A2.1 were targeted for developing high resolution melting (HRM) marker linked with sugar content in strawberry (Table S9). Among these five HRM markers, reasonable match between the phenotypic and genotypic observations was only found for the marker MF154, designed based on the SNP A1 723 G (for high and low sugar contents, respectively) of the UDP-glucose 4-epimerase GEPI48-like gene FAN_iscf00021287 (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…The flanking marker MF472 of QTL qSSC-2B is found within the UDP-glucosyltransferase gene (FAN_iscf00049825.1). One glucose-6-phosphate gene (FANhyb_rscf00000021.1.g00018.1— FaGlu8 ) in addition to ‘UDP-glucose 6-dehydrogenase’ and ‘UDP-glucose 4-epimerase GEPI48-like gene’ (FANhyb_rscf00000538.1.g00003.1- FaGlu15 ) were very recently shown to be upregulated in ripe fruits of high sugar cultivars, Shanmugam et al ( 2017 ) and one ‘glucose 6-phosphate/phosphate translocator 1’ gene ( FaGPT1 ) were also recently found to be expressed in mature fruits of high sugar cultivars, Geumsil, Aram, Maehyang and Okmae (Lee et al 2018 ). The flanking marker MF472 of QTL qSSC-2B is harbored in ‘UDP-glucosyltransferase gene’ (FAN_iscf00049825.1) which may have direct roles in sugar biosynthesis (Tables S7 and S8).…”
Section: Discussionmentioning
confidence: 99%